Superstrong sulfuric acid-resistant nanofiltration membrane, preparation method and application thereof
The ultra-strong sulfuric acid resistant nanofiltration membrane prepared by interfacial polymerization reaction solves the problem of nanofiltration membrane failure in strong acidic environments, achieving a balance between high rejection rate and water flux. It is suitable for the treatment of strong acidic wastewater and has good industrialization prospects.
Patent Information
- Application Number
- CN202511299525.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-12
- Publication Date
- 2025-10-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing nanofiltration membranes are unstable and prone to failure in strongly acidic environments, making them difficult to apply in the treatment of high-concentration sulfuric acid wastewater.
Ultra-strong sulfuric acid resistant nanofiltration membranes were prepared by interfacial polymerization reaction. Amine monomers such as piperazine, m-phenylenediamine, p-phenylenediamine, and ethylenediamine were used with acyl chloride monomers such as trimesoyl chloride and terephthaloyl chloride to form a polyamide-polyurea separation layer with resistance to acid hydrolysis. The degree of crosslinking and density were optimized by combining appropriate process conditions and base membrane materials.
It maintains high rejection rate and water flux in strong acid environments, exhibits excellent acid resistance, and is suitable for the treatment of strongly acidic wastewater. This reduces preparation costs and complexity, and expands its application range.
Smart Images

Figure CN120838197A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of membrane material preparation and membrane separation technology, specifically relating to an ultra-strong sulfuric acid resistant nanofiltration membrane, its preparation method and its application. Background Technology
[0002] Nanofiltration (NF) membranes are a pressure-driven membrane separation technology that falls between ultrafiltration and reverse osmosis. With pore sizes of approximately 0.5-2 nm, they effectively retain divalent ions, organic matter with molecular weights of 200-1000 Da, and heavy metal ions. Because nanofiltration membranes have high rejection rates for multivalent ions but lower rejection rates for monovalent ions, they are widely used in water softening, groundwater hardness removal, desalination, decolorization, odor removal, and heavy metal ion removal. Nanofiltration technology also shows significant application potential in the treatment of acidic wastewater from industries such as chemical, metallurgical, electronics, energy, and battery manufacturing, for example, in the recovery of valuable metals from sulfuric acid solutions, sulfuric acid regeneration from electrolytes in waste lead-acid batteries, and wastewater resource recovery. However, nanofiltration membranes suffer from performance instability and susceptibility to failure under strongly acidic environments. Traditional nanofiltration membranes (especially aromatic polyamide composite membranes) are prone to hydrolysis and structural damage in their selective separation layers during long-term operation under strong acid conditions, leading to a significant decrease in rejection rate and a shortened membrane lifespan. For example, in strong acid solutions such as sulfuric acid, the amide bonds in polyamide membranes break, causing partial disintegration of the separation layer and thus reducing the membrane's separation performance. This acid instability limits the application of nanofiltration technology in the treatment of high-concentration sulfuric acid wastewater.
[0003] To address the issue of insufficient stability of polyamide nanofiltration membranes under strong acid conditions, researchers have proposed various modification strategies in recent years. These mainly include introducing acid-resistant functional groups into the polyamide molecule, selecting novel polymerizable monomers, and constructing composite separation layer structures to improve the membrane's hydrolysis resistance. For example, the team led by Wan Yinhua at the Institute of Process Engineering, Chinese Academy of Sciences, reported a dual-charged acid-resistant nanofiltration membrane. This membrane was created by secondary interfacial polymerization, where a polyamide-polyurethane layer was composited onto a polyamide-sulfonamide separation layer, forming a dual separation layer membrane with a Janus structure. This membrane exhibited retention rates exceeding 93% for both sodium sulfate and magnesium chloride and maintained stable performance even after long-term operation in a 10 wt% sulfuric acid environment. Furthermore, other studies have employed methods such as modification with sulfonic acid-containing amine monomers or nanomaterials to enhance the acid resistance and separation efficiency of nanofiltration membranes.
[0004] While the aforementioned methods have improved the stability of nanofiltration membranes in acidic environments to some extent, they generally suffer from problems such as complex preparation processes, high costs, or difficulty in simultaneously improving acid resistance and achieving high flux and high rejection rates. For example, some acid-resistant membranes experience a decrease in water flux due to excessively high crosslinking density; other methods rely on special monomers or complex modification processes, limiting their large-scale production and application. Therefore, there is an urgent need in current technology to develop a nanofiltration membrane preparation method that is simple in process, low in cost, and simultaneously possesses excellent acid resistance, high rejection rate, and good flux. Summary of the Invention
[0005] The purpose of this invention is to overcome the defects of the prior art and provide a nanofiltration membrane with super sulfuric acid resistance, its preparation method and its application, so as to solve the problem that the nanofiltration membrane in the prior art is unstable and prone to failure in a strong acid environment.
[0006] The specific technical solution of the present invention is as follows: One object of the present invention is to provide an ultra-strong sulfuric acid resistant nanofiltration membrane, comprising a base membrane and a separation layer formed on the upper surface of the base membrane; the separation layer is formed by an interfacial polymerization reaction of an aqueous phase solution and an organic phase solution followed by heat treatment; the solute in the aqueous phase solution includes at least one selected from piperazine, m-phenylenediamine, p-phenylenediamine, ethylenediamine, and polyethyleneimine; the solute in the organic phase solution includes at least one selected from trimesoyl chloride, terephthaloyl chloride, and isophthaloyl chloride; the base membrane is made of at least one selected from polysulfone, polyethersulfone, polyacrylonitrile, and polyvinylidene fluoride; the solute in the organic phase solution also includes toluene diisocyanate.
[0007] The solute in the aqueous solution is piperazine, and the mass fraction of piperazine in the aqueous solution is 1.5%; the solute in the organic solution is trimesoyl chloride, and the weight-volume percentage of trimesoyl chloride in the organic solution is 0.15%-0.2%.
[0008] The solute in the aqueous solution also includes polyethyleneimine, and the mass fraction of polyethyleneimine in the aqueous solution is 1.5%-2.0%.
[0009] The weight-volume percentage of toluene diisocyanate is 0.05%-3.0%.
[0010] The aqueous solution contains piperazine and polyethyleneimine, and the organic solution contains toluene diisocyanate and trimesoyl chloride. The molar ratio of amino groups in the aqueous solution, isocyanate groups in the organic solution, and acyl chloride groups is 1:2:3.
[0011] The minimum volume of the aqueous solution should be sufficient to completely submerge the pretreated base membrane. Generally, to ensure the absorption concentration and absorption effect of the base membrane, it should be 3-5 times the minimum volume. The same applies to the oil phase solution, which should also be 3-5 times the minimum volume.
[0012] A second objective of this invention is to provide a method for preparing an ultra-strong sulfuric acid-resistant nanofiltration membrane, comprising the following steps: S1. Wash and soak the base film with water to remove impurities and protective liquid from the pores of the base film. After taking out the base film, remove excess water from the surface to obtain the pretreated base film. S2. Prepare an aqueous solution of amine monomers, and contact the pretreated base membrane with the aqueous solution to adsorb the amine monomers on the surface and pores of the base membrane. Then remove the excess aqueous solution from the surface of the base membrane. S3. Prepare an organic phase solution containing organic monomers, and bring the base film treated in S2 into contact with the organic phase solution to carry out an interfacial polymerization reaction for 5-90 seconds. S4. The membrane after the interfacial polymerization reaction is post-treated, including heat treatment and cleaning, to obtain the ultra-strong sulfuric acid resistant nanofiltration membrane.
[0013] The time for the interfacial polymerization reaction described in S3 is 30-60 seconds.
[0014] In S4, the heat treatment temperature is 40-90℃ and the time is 5-20 minutes.
[0015] The nanofiltration membrane has an initial rejection rate greater than 98%, a rejection rate retention rate of over 97%, and a water flux of 180 L / (m²). 2 ·h).
[0016] The third objective of this invention is the application of ultra-strong sulfuric acid resistant nanofiltration membranes in the treatment, recovery, reuse, and recycling of acidic wastewater.
[0017] The base membrane is a porous polymer ultrafiltration membrane, such as an ultrafiltration substrate membrane made of polysulfone (PSF), polyethersulfone (PES), polyacrylonitrile (PAN), polytetrafluoroethylene (PTFE), or polyvinylidene fluoride (PVDF). The base membrane provides mechanical support, and its surface pore size and morphology also affect the quality of the separation layer formed by interfacial polymerization. This invention preferably uses a smooth-surfaced, uniformly pore-sized PVDF ultrafiltration base membrane to facilitate the formation of a continuous and dense polyamide layer. Other suitable base membranes are also acceptable.
[0018] The organic solvents used in the organic phase are n-hexane, cyclohexane, and petroleum ether.
[0019] Small amounts of additives can be added to the aqueous or organic phase as needed to improve interfacial polymerization and membrane performance. For example, a phase transfer catalyst (such as triethylamine TEA) or an acid acceptor (such as sodium hydroxide) can be added to the aqueous phase to neutralize the HCl generated during the reaction and promote polymerization. Surfactants can also be added to reduce interfacial tension and allow monomers to contact better. In addition, nanomaterials (such as graphene oxide, silica nanoparticles, etc.) can be introduced as fillers to prepare thin-film nanocomposite (TFN) membranes to improve the membrane's hydrophilicity, mechanical strength, or acid resistance. For example, heteropolyacid-functionalized SiO2 nanoparticles can be dispersed in a piperazine aqueous phase and then interfacially polymerized to prepare an acid-resistant nanofiltration membrane. The silanol groups on the SiO2 surface are protonated / hydrated under acidic conditions, which can slow down the dissociation of amide bonds, thereby improving the membrane's acid resistance.
[0020] The present invention also has the following alternatives: Monomer Substitution: In addition to the commonly used monomers mentioned above, other amine or acyl chloride monomers with acid-resistant functional groups can be selected. For example, amine monomers containing sulfonic acid groups (such as p-aminobenzenesulfonic acid, sulfonated piperazine, etc.) can be used to partially replace ordinary amine monomers, giving the polyamide chain a sulfonic acid group (–SO3H). The acidity of sulfonic acid groups is much stronger than that of carboxylic acid groups, and the sulfonamide bonds formed are less likely to break in acids. Introducing a sulfonamide structure into the polyamide network can significantly improve the acid resistance of the membrane. Alternatively, fully aromatic polyamines (such as 1,3,5-tris(4-aminophenyl)benzene) or heterocyclic amines (such as melamine) can be reacted with TMC to form highly conjugated or heterocyclic polyamides, thereby enhancing hydrolysis resistance. Regarding organic phase monomers, in addition to TMC, aromatic polysulfonyl chlorides (such as isophenylene disulfonyl chloride) can also be tried with amines to form polysulfonamide membranes, which exhibit better stability under strong acids. Monomer combinations capable of forming acid-resistant polymer networks are also within the scope of this invention.
[0021] Process Condition Optimization: The interfacial polymerization conditions of this invention can be adjusted as needed. For example, the crosslinking density can be controlled by changing the monomer concentration ratio of the aqueous phase to the organic phase. Increasing the concentration of amine monomers or acyl chloride monomers usually increases the reaction rate and degree of crosslinking, but excessively high concentrations may lead to excessively thick membranes or defects. Alternatively, stepwise interfacial polymerization (multiple alternating coatings of the aqueous and organic phases) can be used to construct multilayer polyamide structures, thereby obtaining thicker or gradient separation layers. Furthermore, temperature control can be introduced during interfacial polymerization; lowering the reaction temperature can slow down monomer diffusion and the reaction rate, which is beneficial for forming a more uniform and thinner polyamide layer. By lowering the organic phase temperature to -10 to -20°C, nanofiltration membranes with smoother surfaces and thinner separation layers can be prepared. Therefore, this invention does not exclude the use of low-temperature interfacial polymerization and other processes to further improve membrane performance.
[0022] In addition, the base film can be pretreated and modified (such as plasma treatment or surface coating modification) to improve its bonding strength with the separation layer and the interfacial polymerization effect.
[0023] Membrane module form: This patent currently describes the preparation of a flat sheet membrane, but the resulting acid-resistant nanofiltration membrane can also be applied to other module forms, such as spiral wound membrane elements and hollow fiber membranes. For hollow fiber nanofiltration membranes, interfacial polymerization can be performed by sequentially passing monomer solutions into the fiber lumen or coating them onto the outer surface of the fiber to form a composite hollow fiber nanofiltration membrane. These different membrane module forms do not affect the essence of this invention; they are merely differences in application.
[0024] Compared with the prior art, the beneficial technical effects of this invention are reflected in: 1. Excellent resistance to sulfuric acid This invention significantly improves the chemical stability of the membrane under strong acid conditions by optimizing the composition and process of the polymer monomers. After being immersed in 20% sulfuric acid for 100 days, the nanofiltration membrane still maintains a magnesium sulfate rejection rate of over 98%, indicating that it has excellent long-term acid resistance and overcomes the problem of easy hydrolysis and failure of traditional polyamide nanofiltration membranes under low pH conditions.
[0025] 2. Excellent separation performance This invention achieves high acid resistance while also maintaining good selective separation capability and water flux. The nanofiltration membrane exhibits a rejection rate of over 97% for divalent salts (such as magnesium sulfate) and a lower rejection rate for monovalent salts (such as sodium chloride), displaying typical nanofiltration separation characteristics; simultaneously, its water flux reaches 180 L / (m³). 2 ·h), which greatly improves the dual requirements of throughput and rejection rate in practical applications.
[0026] 3. The preparation process is simple and easy to scale up. This invention employs a conventional interfacial polymerization process, which is simple, mild, and suitable for continuous production. The method requires no complex modification steps or special equipment, uses low-cost and readily available raw materials, significantly reducing the difficulty and cost of film formation, and possesses promising prospects for industrial application.
[0027] 4. Wide range of applications This membrane is suitable for various highly acidic environments, such as pickling wastewater, electroplating wastewater, and hydrometallurgical leaching solutions, for acid recovery and heavy metal ion concentration and separation. It does not require pre-neutralization treatment, which simplifies the process and reduces operating costs and solid waste generation. It has important application value in the fields of resource recycling and pollution control.
[0028] This invention enables the generated polyamide backbone or side groups to have acid hydrolysis resistance by selecting appropriate amine monomers and acyl chloride monomers; at the same time, the degree of crosslinking and compactness of the membrane are controlled by controlling monomer concentration, reaction time and temperature, thereby improving the acid resistance stability of the membrane while ensuring high rejection rate.
[0029] Meanwhile, the isocyanate groups (-NCO) in toluene diisocyanate react with the -NH2 groups in the amine monomers to form polyurea bonds, which themselves possess excellent hydrolysis resistance. These polyurea bonds and the amide bonds in the polyamide chains form cross-links, constructing a stable three-dimensional network structure. This structure not only enhances the mechanical strength of the membrane material but also significantly improves its resistance to erosion in acidic environments, thereby comprehensively improving the durability and separation performance stability of the nanofiltration membrane under harsh operating conditions. Attached Figure Description
[0030] Figure 1 This is a high-magnification SEM image of the ultra-strong sulfuric acid resistant nanofiltration membrane with a thickness of 250 nanometers in Example 1. Detailed Implementation
[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0032] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0034] The embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0035] The raw material specifications used in this embodiment of the invention are as follows: Raw materials and reagents: Polysulfone PSF ultrafiltration membrane, molecular weight cutoff 10 kDa, self-made; Piperazine PIP, analytical grade; Polyethyleneimine (PEI), analytical grade; Trimethylbenzenetriformyl chloride (TMC), analytical grade; Toluene diisocyanate (TDI), analytical grade; n-Hexane HPLC grade; Deionized water.
[0036] Example 1 Preparation steps: 1. Cut the PSF base film into 10 cm × 10 cm squares, rinse with deionized water, and then soak in deionized water for 30 minutes to remove the glycerol protective solution and impurities from the membrane pores. After removing it, gently roll it with a clean, soft rubber roller to remove excess moisture from the membrane surface, keeping the membrane slightly damp.
[0037] 2. Preparation of the aqueous solution: Dissolve PIP and PEI in deionized water, and mix them thoroughly to prepare an aqueous solution with a PIP mass fraction of 1.5% and a PEI mass fraction of 2.0%. Lay the base membrane flat on a clean glass plate, and use a pipette to evenly add the aqueous solution to the membrane surface, ensuring complete wetting. Let it stand for 2 minutes to allow the PIP and PEI to be fully adsorbed onto the membrane surface and pores. Then pour off the remaining aqueous solution and gently press the membrane surface with a rubber roller to remove excess liquid.
[0038] 3. Preparation of the organic phase solution: Dissolve TMC and TDI in n-hexane, with TMC concentration at 0.15% (w / v) and TDI concentration at 0.05% (w / v). Quickly pour the organic phase solution onto the substrate membrane surface, which still has a thin layer of water, ensuring that the organic phase covers the entire membrane surface. A white film will immediately appear at the interface between the two phases; this is the polyamide-polyurea separation layer. Maintain the organic phase coverage for 45 seconds to allow the polymerization reaction to proceed fully.
[0039] 4. Discard the remaining organic phase solution and allow the membrane to stand in the air for 2 minutes to allow any residual hexane to evaporate. Then, place the membrane in a 60°C oven for 15 minutes to further crosslink and solidify the separation layer.
[0040] 5. After heat treatment, remove the membrane and cool it to room temperature. Then immerse it in deionized water for 1 hour to wash away residual monomers and byproducts. The prepared nanofiltration membrane is stored in deionized water for later use.
[0041] The nanofiltration membrane prepared in this embodiment has a thickness of 250 nanometers. A high-magnification SEM image is shown below. Figure 1 As shown. (Through) Figure 1 It can be seen that: (1) the acid-resistant film can be successfully prepared according to Example 1; (2) the thickness of the successfully prepared acid-resistant film layer is 250nm; (3) the base film is below the 250nm acid-resistant film layer, and the base film supports the 250nm acid-resistant film layer on its surface.
[0042] Performance testing: The sulfuric acid resistant nanofiltration membrane prepared above was loaded into a small laboratory nanofiltration evaluation device to test its separation performance and acid resistance.
[0043] Test conditions: Effective membrane area 0.002 m² 2 The operating pressure was 0.15 MPa, and the feed temperature was 25℃. First, the membrane was pre-pressurized with deionized water for 30 minutes to stabilize its performance. Then, the following feed solutions were introduced for filtration tests: Pure water flux: The measured pure water permeation flux was 24 L / (m²). 2 ·h).
[0044] Salt rejection rate: The membrane rejection rates were measured using 2000 mg / L magnesium sulfate solution and 2000 mg / L sodium chloride solution as feed solutions. The results showed that the rejection rate for magnesium sulfate was 99.7%, while the rejection rate for NaCl was 41%. This indicates that the membrane has high selectivity for divalent anions, which is consistent with the expectations of the ultra-strong sulfuric acid resistant nanofiltration membrane of this invention.
[0045] Sulfuric acid resistance: A magnesium sulfate solution containing 15 wt% sulfuric acid (MgSO4 concentration 2000 mg / L) was prepared as the feed solution and continuously filtered at 0.5 MPa for 24 hours, with samples taken every 4 hours to determine the MgSO4 rejection rate. The initial rejection rate was 99.7%, and after 24 hours, the rejection rate remained at approximately 97.4%, without significant decrease. Subsequently, the membrane was removed and immersed in a 15 wt% sulfuric acid solution at room temperature for 7 days. The MgSO4 rejection rate was then tested again, and the result was 97.2%, essentially the same as before immersion. This demonstrates that the membrane's performance remains stable after long-term immersion in high-concentration sulfuric acid, exhibiting excellent acid resistance.
[0046] Example 2 Effects of different monomer combinations on membrane performance Following the method of Example 1, a series of nanofiltration membrane samples were prepared by changing the monomer composition of the aqueous and organic phases, respectively, to investigate the effect of monomers on membrane performance. The specific scheme is as follows: Sample A: Aqueous phase 1.5% PIP, organic phase 0.2% TMC (no TDI). This is the most traditional piperazine-pyromellitic chloroformamide membrane. (Control / Comparison Group) Sample B: The aqueous phase consisted of 1.5% PIP + 2.0% PEI (mixed amines), and the organic phase consisted of 0.15% TMC + 0.05% TDI (formulation of Example 1).
[0047] Sample C: The aqueous phase consisted of 1.5% PIP + 2.0% PEI (mixed amines), and the organic phase consisted of 0.15% TMC + 1.5% TDI.
[0048] Sample D: The aqueous phase consisted of 1.5% PIP + 2.0% PEI (mixed amines), and the organic phase consisted of 0.15% TMC + 3.0% TDI.
[0049] Sample E: Aqueous phase: 1.5% PIP; Organic phase: 0.15% TMC + 0.05% TDI.
[0050] Sample F: Aqueous phase: 1.5% PIP + 1.5% PEI (mixed amines); Organic phase: 0.20% TMC.
[0051] The preparation steps and post-treatment conditions for all samples were the same as in Example 1. The membranes obtained were tested for retention stability in a sulfuric acid environment.
[0052] Test method: Each membrane was immersed in 15 wt% H2SO4 solution for 72 hours, and then its MgSO4 rejection rate was measured and compared with the rejection rate before immersion to calculate the retention rate.
[0053] The test method for scouring resistance time is as follows: at room temperature, the nanofiltration membrane is scoured with an electrolyte of 20% H2SO4 at a cross-flow speed of 7 m / s, and the time for the nanofiltration membrane to disintegrate is recorded.
[0054] The results are shown in Table 1: Table 1. Comparison of membrane performance under different monomer combinations
[0055] The data in the table show that the traditional polyamide membrane (sample A) exhibited a significant decrease in retention rate after immersion in strong acid, with a retention rate of only 94%. In contrast, samples B, C, D, E, and F, which incorporated modified monomers, all demonstrated better acid resistance, with retention rates of 97% or higher. Samples B, C, and D (polyamide-polyurea membranes containing different concentrations of TDI) showed almost no performance loss, with retention rates approaching 100%. This verifies the effectiveness of this invention in improving membrane acid resistance through multi-phase (aqueous) and multi-phase (oil) monomer modifications. Furthermore, the initial retention rates of all samples were above 97%, indicating that these improvements did not come at the expense of membrane separation performance. After 450 hours of scouring experiments, sample A disintegrated and failed. Samples E and F showed significantly improved scouring resistance compared to sample A. Meanwhile, samples B, C, and D, with added TDI, exhibited scouring resistance times of 3000, 4200, and 5100 hours, respectively, which are 7, 9.3, and 11.3 times that of sample A, demonstrating excellent resistance to strong acid solutions. Furthermore, comparing the results of samples B (TDI concentration 0.05%), C (TDI concentration 1.5%), and D (TDI concentration 3.0%) in Table 1 shows that appropriately increasing the TDI concentration from 0.05% to 1.5%, and then to 3.0%, can increase the number of polymer branches, enhance the stability of the material after network cross-linking, and allow for a moderate excess of TDI in the chemical reaction. This promotes the reaction towards the product, resulting in a denser and more complete film material, further extending the resistance to strong acid solutions.
[0056] Example 3 Application test of sulfuric acid resistant nanofiltration membrane To verify the effectiveness of the membrane of this invention in the treatment of actual acidic wastewater, waste electrolyte from a waste lead-acid battery dismantling workshop was selected for testing. This wastewater contained approximately 800 mg / L PbSO4, approximately 145 g / L H2SO4, and a pH ≈ 0.05. The sulfuric acid-resistant nanofiltration membrane prepared in Example 1 was used to assemble a small spiral-wound membrane element with an effective area of approximately 0.45 m². 2 The waste liquid was subjected to circulation and concentration treatment under operating pressure of 0.6 MPa and cross-flow velocity of 1.2 m / s.
[0057] Approximately 10 L of waste electrolyte from spent lead-acid batteries was added to the feed tank. The circulation pump and high-pressure pump were then turned on, causing the electrolyte to circulate and filter within the membrane module. Permeate (acid) was continuously discharged from the membrane module, while the concentrate was returned to the feed tank. The liquid level in the tank gradually decreased, and the concentration gradually increased. A total of approximately 5.7 L of permeate was collected, with an H2SO4 concentration of 180 g / L and a Pb concentration of... 2+The concentration was only about 3.2 mg / L. This indicates that most of the sulfuric acid permeated through the membrane and could be recovered, while lead ions were retained and concentrated in the feed solution. This also demonstrates that the membrane of this invention has an extremely high retention effect on heavy metal ions, effectively retaining them in the concentrate for subsequent recovery. This experiment proves that the sulfuric acid-resistant nanofiltration membrane of this invention can efficiently separate and recover acid and heavy metals from acidic wastewater: on the one hand, the permeate is high-concentration sulfuric acid, which can be reused in production or further purified and recycled; on the other hand, the concentrate is rich in heavy metal sulfates, and metal resources can be recovered through methods such as heavy metal crystallization. This not only reduces wastewater discharge but also achieves resource recycling, resulting in significant environmental and economic benefits.
[0058] The above detailed description is a specific description of one feasible embodiment of the present invention. This embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not depart from the present invention should be included in the scope of the technical solution of the present invention.
[0059] It should be particularly noted that the various embodiments listed in this specification and accompanying drawings are intended to illustrate the technical solutions and advantages of the present invention, and not to limit the scope of protection of the present invention. Without departing from the core ideas and technical effects of the present invention, those skilled in the art can make any form of improvement, substitution, combination, or modification to the structural arrangement, process parameters, material selection, control logic, etc., of the described embodiments; any obvious changes based on the same concept should be considered equivalent solutions of the present invention and should be included within the scope of protection defined by the claims of the present invention. The actual scope of protection of the present invention is determined by the appended claims and should be correctly understood in conjunction with the specification and accompanying drawings.
Claims
1. A super-strong sulfuric acid resistant nanofiltration membrane, characterized in that, Includes a base film and a separation layer formed on the upper surface of the base film; The separation layer is formed by interfacial polymerization of an aqueous solution and an organic solution followed by heat treatment. The solute in the aqueous solution includes at least one of piperazine, m-phenylenediamine, p-phenylenediamine, ethylenediamine, and polyethyleneimine; The solute in the organic phase solution includes at least one of pyromellitic phthaloyl chloride, terephthaloyl chloride, and isophthaloyl chloride; The base film is made of at least one of polysulfone, polyethersulfone, polyacrylonitrile, polytetrafluoroethylene, and polyvinylidene fluoride. The solute in the organic phase solution also includes toluene diisocyanate.
2. The ultra-strong sulfuric acid resistant nanofiltration membrane according to claim 1, characterized in that, The solute in the aqueous solution is piperazine, and the mass fraction of piperazine in the aqueous solution is 1.5%; the solute in the organic solution is trimesoyl chloride, and the weight-volume percentage of trimesoyl chloride in the organic solution is 0.15%-0.2%.
3. The ultra-strong sulfuric acid resistant nanofiltration membrane according to claim 2, characterized in that, The solute in the aqueous solution also includes polyethyleneimine, and the mass fraction of polyethyleneimine in the aqueous solution is 1.5%-2.0%.
4. The ultra-strong sulfuric acid resistant nanofiltration membrane according to claim 2 or 3, characterized in that, The toluene diisocyanate in the organic phase solution has a weight-volume percentage of 0.05%-3.0%.
5. The ultra-strong sulfuric acid resistant nanofiltration membrane according to claim 4, characterized in that, The aqueous phase solution contains piperazine and polyethyleneimine, and the organic phase solution contains toluene diisocyanate and trimesoyl chloride. The molar ratio of amino groups in the aqueous phase solution, isocyanate groups in the organic phase solution, and acyl chloride groups is 1:2:
3.
6. A method for preparing an ultra-strong sulfuric acid resistant nanofiltration membrane as described in any one of claims 1-5, characterized in that, The following steps are involved: S1. Wash and soak the base film with water to remove impurities and protective liquid from the pores of the base film. After taking out the base film, remove excess water from the surface to obtain the pretreated base film. S2. Prepare an aqueous solution of amine monomers, and contact the pretreated base membrane with the aqueous solution to adsorb the amine monomers on the surface and pores of the base membrane. Then remove the excess aqueous solution from the surface of the base membrane. S3. Prepare an organic phase solution containing organic monomers, and bring the base film treated in S2 into contact with the organic phase solution to carry out an interfacial polymerization reaction for 5-90 seconds. S4. The membrane after the interfacial polymerization reaction is post-treated, including heat treatment and cleaning, to obtain the ultra-strong sulfuric acid resistant nanofiltration membrane.
7. The method for preparing the ultra-strong sulfuric acid resistant nanofiltration membrane according to claim 6, characterized in that, The time for the interfacial polymerization reaction described in S3 is 30-60 seconds.
8. The method for preparing the ultra-strong sulfuric acid resistant nanofiltration membrane according to claim 6, characterized in that, In S4, the heat treatment temperature is 40-90℃ and the time is 5-20 minutes.
9. The ultra-strong sulfuric acid resistant nanofiltration membrane according to claim 1, characterized in that, The nanofiltration membrane has an initial rejection rate greater than 98%, a rejection rate retention rate of over 97%, and a water flux of 180 L / (m²). 2 ·h).
10. The application of an ultra-strong sulfuric acid resistant nanofiltration membrane as described in any one of claims 1-5 in the treatment, recovery, reuse, and recycling of acidic wastewater.
Citation Information
Patent Citations
Acid / alkali-resistant composite nanofiltration membrane as well as preparation method and application thereof
CN113509839A
Acid-resistant nanofiltration membrane as well as preparation method and application thereof
CN115970521A
Acid-resistant nanofiltration membrane containing polyurea structure and preparation method thereof
CN117181027A
Acyl chloride-containing isocyanate monomer, preparation method thereof and application of acyl chloride-containing isocyanate monomer in acid-resistant nanofiltration membrane
CN118206470A
Acid- and alkali-resistant composite nanofiltration membrane, and preparation method therefor and use thereof
WO2024120196A1
Cited By
Acid-resistant polyamide nanofiltration membrane and arsenic removal application thereof in hair dye preparation
CN121244029A
Polyamide acid-resistant nanofiltration membrane and its application in arsenic removal in hair dye preparation
CN121244029B